PEMBUATAN DESAIN KOLAM IKAN BANDENG BERBASIS KONSEP BIOSECURITY BAGI MASYARAKAT PETANI TAMBAK DI PESISIR KABUPATEN DEMAK - M. Anas Dzakiy; Achmad Buchori; Fafa Nurdyansyah; Rumiyatun Istiyaningsih; Velma Nindita (Journal of Dedicators Community, 2017)
The villagers of Wonoagung, Sub-district Karangtengah at Demak Regency is the farmer Community, especially in terms of milkfish farming. The problems is inadequate harvest of milkfish farming. This is because the low level of cultivation techniques and an understanding of the threat of disease and pest predators to milkfish. To find the solution of the problems of the milkfish farmers, training and workshops about the concept of Biosecurity for the farmers has been implemented. The enthusiasm of the farmers look very high, many of the problems surrounding the Milkfish cultivation could be answered. The application of Biosecurity are becoming the perfect solution for the Milkfish farmers in the village of Wonoagung Sub-district Karangtengah at Demak Regency in dealing with the threat of either disease and pest predators. The concept of Biosecurity that applied on farmed land must include the territorial of waters, air and land of the milkfish environmental farming. Keywords : The Milkfish, Wonoagung Village, Biosecurity